Bibliometrics and Visualization of the Mechanisms of Parkinson's Diseases Based on Animal Models - Wang, Yan-Qiu; Chen, Yi-Bing; Xu, Dong; Cui, Yuan-Lu (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: Energy metabolism disorder is one of the causes of Parkinson's disease (PD). Rodents, such as rats and mice are often used to establish animal models of PD. This paper used a bibliometric method to analyze the studies of rat and mouse PD models published between 2009 and 2018 in the Web of Science (WOS) database using CiteSpace V software. In addition, we conducted a literature review on the development status and research hotspots in this field in the past ten years. Methods: The related articles on rat and mouse PD models were retrieved from the WOS database, and an analysis of the keywords in these articles was conducted using CiteSpace V. A timeline graph was developed by the software in order to show the focus of researchers in the PD field. Results: A total of 8,636 articles were obtained. Results of the cluster analysis in the PD field such as neuroinflammation, oxidative stress, and autophagy, contributed to the systematic review about the pathogenesis of PD. At the same time, based on the property of the model drug, this review has summarized and compared different administration techniques and mechanisms of 6-hydroxydopamine (6- OHDA), 1-methyl-4-phenyl-1, 2, 4, 5-tetrahydropyridine (MPTP), paraquat and rotenone. Conclusion: According to the bibliometric analysis, studies on PD were focused on the mechanisms of oxidative stress, neuroinflammation, and autophagy. Activated microglia releases inflammatory cytokines; mitochondrial dysfunction is caused by oxidative damage of mitochondrial protein; abnormal autophagy-lysosome pathway can lead to abnormal protein deposition in dopaminergic neurons. In addition, although many animal models of PD have been established, there are some limitations of such models. Therefore, it is necessary to develop models that accurately mimic human PD.
Keywords: MPTP